Dynamic crack analysis in piezoelectric solids under time-harmonic loadings with a symmetric Galerkin boundary element method. (November 2017) - Wünsche, M.; Sladek, J.; Sladek, V.; Zhang, C.; García-Sánchez, F.; Sáez, A.
Abstract: This paper presents the dynamic crack analysis in two-dimensional (2D) and linear piezoelectric composites. Stationary cracks in infinite and finite piezoelectric solids subjected to different time-harmonic loadings are investigated. A symmetric Galerkin boundary element method (SGBEM) is developed for this purpose. The frequency-domain fundamental solutions for linear piezoelectric solids are utilized. The double boundary integrals are computed analytically for straight elements to enhance the efficiency of the present SGBEM. Non-linear electrical crack-face boundary conditions are applied to take the limited electrical permeability of the crack into account. Numerical examples are presented and discussed to show the accuracy of the presented frequency-domain SGBEM and the influences of the coupled fields on the dynamic field intensity factors.